2019
DOI: 10.1007/s10461-019-02410-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes Over Time in HIV Prevalence and Sexual Behaviour Among Young Female Sex-Workers in 14 Sites in Zimbabwe, 2013–2016

Abstract: Young female sex-workers (FSW) aged 18–24 are at high risk of HIV due to high numbers of sexual partners, difficulty negotiating condom use, increased risk of gender-based violence, and limited access to services. Here we describe changes in sexual behaviours among young FSW across Zimbabwe between 2013 and 2016, and risk factors for prevalent HIV in 2013 and 2016. FSW ≥ 18 years were recruited using respondent-driven sampling in 14 sites across Zimbabwe in 2013 and 2016 as part of the SAPPH-IRe trial. We coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 32 publications
(46 reference statements)
5
25
0
Order By: Relevance
“…This could be a concern, knowing that several studies have also found that younger women and sex workers could be at higher risk of HIV infection than their older peers. 23,24 Our results showed high uptake or interest and very good retention rates, supporting a successful implementation of PrEP among FSWs in Senegal. Other recently conducted PrEP demonstration projects in sub-Saharan Africa have had variable success of uptake, but lower retention rates of FSWs.…”
Section: Discussionsupporting
confidence: 52%
“…This could be a concern, knowing that several studies have also found that younger women and sex workers could be at higher risk of HIV infection than their older peers. 23,24 Our results showed high uptake or interest and very good retention rates, supporting a successful implementation of PrEP among FSWs in Senegal. Other recently conducted PrEP demonstration projects in sub-Saharan Africa have had variable success of uptake, but lower retention rates of FSWs.…”
Section: Discussionsupporting
confidence: 52%
“…Only a small number of HIV-positive AGYW, mainly from urban areas, were involved in sex work and they were either divorced or single. Young HIV-positive sex workers are at substantial risk of disease progression if they do not engage in HIV prevention and treatment, which could contribute to the worsening of the local HIV epidemic [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in Eastern and Southern Africa, women who sell sex are three times more likely to be living with HIV than other women of reproductive age [2]. Although less is known about young women who sell sex (YSW), a growing body of literature from SSA suggests a high incidence and burden of HIV by age 24 among YSW stemming from early experience of sexual, structural, and reproductive health vulnerabilities [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%